Bowel and Bladder Reproducibility in Image Guided Radiation Therapy for Prostate Cancer: Results of a Patterns of Practice Survey - Lindsay S. Rowe, MD; Jeremy J. Mandia, MD; Kilian E. Salerno, MD; Uma T. Shankavaram, PhD; Shaoli Das, PhD; Freddy E. Escorcia, MD, PhD; Holly Ning, PhD; Deborah E. Citrin, MD (Advances in Radiation Oncology, 2022)
Purpose: Optimal management of patients with prostate cancer (PCa) to achieve bowel and bladder reproducibility for radiation therapy (RT) and the appropriate planning target volume (PTV) expansions for use with modern image guidance is uncertain. We surveyed American Society of Radiation Oncology radiation oncologists to ascertain practice patterns for definitive PCa RT with respect to patient instructions and set up, daily image guidance, and subsequent PTV expansions. Methods and Materials: A pattern of practice survey was sent to American Society of Radiation Oncology radiation oncologists who self-identified as specializing in PCa. Respondents identified the fractionation regimens routinely used, and their practices regarding diet, bowel, and bladder instructions for patients with PCa before RT simulation and throughout treatment. Questions regarding PTV margins, daily set up practices, and use of image guidance were included. Results: Of 190 respondents, 158 reported using conventional fractionation (CFx), 49 moderate hypofractionation (MHFx), and 61 stereotactic body radiation therapy (SBRT). Diet modifications during RT were advised by 84% of respondents, treatment with full bladder by 96%, and bowel instructions by 78%. Prescription of bowel medication was higher for respondents using SBRT (95.1%) versus those using CFx/MHFx (55.1%; 34.7%). The most common implantable device reported was fiducial markers, with increased use in SBRT (86.0%; 68.9%) versus CFx/MHFx. Cone beam computed tomography was the most common daily imaging technique across fractionation regimens. SBRT showed correlation between PTV margin expansions, fiducial marker use, and image guidance. Conclusions: Survey results indicate heterogeneity in treatment modality, dose, patient instructions, and PTV expansions used by radiation oncologists in the treatment of patients with PCa. Further investigation to define appropriate patient instructions on bowel preparation to maximize target reproducibility in PCa is needed, as is continued guidance on evidence-based approaches for image guidance and PTV margin selection.